Some observations on the origins of the Dome of the Rock - Omer, Spahic (Kulliyyah of Architecture and Environmental Design, IIUM, 2015)
This paper challenges an old belief that the Dome of the Rock in Jerusalem was built between 65/684 and 72/691 by the Umayyad caliph ‘Abd al-Malik b. Marwan. The paper is divided into two parts. The first part briefly examines the significance of the Rock (sakhrah). Therein it is shown that the Rock (Sakhrah) has no special religious significance whatsoever. The second part tries to answer who exactly built the Dome of the Rock and when. The paper concludes that the likely truth is that the caliph ‘Abd al-Malik b. Marwan was able to commence building the edifice only after crushing the insurgence of ‘Abdullah b. al-Zubayr in 73/692. Such were the socio-political conditions in the Muslim state during the insurgency that the caliph’s actions could not transcend the planning and basic preparatory stages, at most. Whether the caliph ‘Abd alMalik b. Marwan was capable of completing the structure during his lifetime or not, remained a debatable point as well. The task of building one of the first and at the same time greatest masterpieces in Islamic architecture might have been completed by his son and successor, al-Walid b. ‘Abd al-Malik. What follows is shedding more light on these aspects of the topic.